Airway leech infestation masquerading as a tumor: a rare case report - Li, Pengyu; Chen, Xianmeng; Chen, Wanling; Huang, Yunchao; Tan, Xiangxiu; Chen, Ying (Frontiers in Oncology, 2025)
Airway obstruction is a ventilatory dysfunction caused by internal and external diseases of the respiratory tract, which is usually considered a life-threatening clinical emergency. Traditionally, airway obstruction can be caused by respiratory tumors, trauma, and foreign bodies, among which tumors are the most common. Consequently, physicians may prioritize tumor-related diagnoses, potentially leading to the misdiagnosis of rare non-neoplastic conditions. Here, we report a case of a 61-year-old adult traveler who initially presented with mild dyspnea and a bronchial space-occupying lesion on a CT scan, raising suspicion of an airway tumor. However, further examination confirmed the diagnosis of a living leech infestation in the bronchus, resulting from a trip to Laos. This case highlights the importance of thorough history-taking and critical thinking in clinical diagnosis, urging physicians to avoid overreliance on intuition or experience alone.